(untitled) (Journal of Management and Social Sciences, 2021)
Over the years, there exists an on-going conflict about women’s right to political administration of her country or community where she finds herself. It is becoming a great concern to many that women are relatively deprived of their rights to politics and even a burning issue in the different parts of the world. Although some elites have taken it as mere propaganda being blown out of proportion usually because of reasons such as religious or cultural inclination, the fact remains that women are not equal to men in Nigerian politics and other countries of the world. The fact is that when women’s rights asserted are being stood upon, the expectation from women participation in politics would hinder the progress of the country. Therefore, this position paper considers educating women on effective participation in Nigerian politics and the impact of women in politics. Suggestions to eliminating women deprivation were discussed and recommendations towards improving the level of women participation in Nigerian politics were made. Keywords Educating, women, gender participation, politics